Proposing a Strategy for Attracting Foreign Direct Investment in Venture Capital Funds - Azizabadi, Ali; Vakili Fard, Hamid Reza; Moradi, Zahra; Keramati, Mohammad Ali (Management Strategies and Engineering Sciences, 2025)
This study proposes a strategy for attracting foreign direct investment (FDI) in venture capital funds. The objective of this research is to identify and analyze the factors that can facilitate or constrain the attraction of foreign investments into venture capital funds. To this end, the study adopts a qualitative approach using the grounded theory methodology. Data were collected through questionnaires and semi-structured interviews with managers and experts active in the venture capital sector. The findings of the research indicate that several key factors directly influence the attraction of FDI. These factors include the economic and financial environment, the legal and regulatory framework, public and private institutions, organizational and managerial culture, access to technology and innovation, barriers and challenges, and the country’s brand and image. Among these, the economic and financial environment—particularly economic stability and investment return rates—exerts the most significant impact on attracting FDI. Additionally, a suitable organizational culture and strategic managerial approach within venture capital funds are identified as facilitating factors for attracting foreign investment. Moreover, access to advanced technologies and innovation is also recognized as one of the influential factors in attracting FDI. A comparison of the results with previous research reveals that these findings are consistent with earlier studies, especially regarding the impact of economic stability, transparent regulations, and innovation on attracting foreign investment. This study recommends that managers of venture capital funds and economic policymakers focus on improving economic conditions, creating transparent and supportive legal frameworks, and promoting a culture of innovation and cooperation between public and private institutions. Such measures can enhance the attraction of foreign investments and improve the economic growth and competitiveness of venture capital funds.